1997
DOI: 10.1074/jbc.272.34.21227
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effect of Intracellular Ca2+ and Protein Kinase C on the Expression of Inwardly Rectifying K+Channel 1 in Mouse Skeletal Muscle

Abstract: The level of inwardly rectifying K ؉ channel 1 (IRK1) mRNA decreased upon denervation and increased during muscle differentiation in mouse skeletal muscle. To identify the mechanism(s) underlying the regulation of IRK1 mRNA expression, we examined its expression using the well differentiated C2C12 mouse skeletal muscle cell line as a model system. Since nerve-induced muscle activity results in contraction, it was questioned whether the changes in IRK1 expression might be relevant to the increased intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…However, the intracellular pathways that transduce these signals to the nucleus are only beginning to be understood. Previous reports have suggested that calcium-activated signaling cascades may play an important role in intracellular signaling during myocyte differentiation (7,11,13,25,26). Using C2C12 cells as a model of myocyte differentiation, we demonstrate that the maintenance of normal intracellular calcium concentrations is vital to myocyte gene expression and differentiation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, the intracellular pathways that transduce these signals to the nucleus are only beginning to be understood. Previous reports have suggested that calcium-activated signaling cascades may play an important role in intracellular signaling during myocyte differentiation (7,11,13,25,26). Using C2C12 cells as a model of myocyte differentiation, we demonstrate that the maintenance of normal intracellular calcium concentrations is vital to myocyte gene expression and differentiation.…”
Section: Discussionmentioning
confidence: 80%
“…For example, calpain-mediated protein degradation appears to allow cell fusion and differentiation of C2C12 cells (13). In addition, increased levels of intracellular calcium appear to stabilize mRNA encoding the inward-rectifying potassium channel 1 (26).…”
Section: Discussionmentioning
confidence: 99%
“…In embryonic amphibian skeletal muscle, I IR development is suppressed by blocking spontaneous activity and accelerated by providing activity at abnormally early stages (338,339). In mammalian skeletal muscle, innervation upregulates and denervation downregulates I IR expression (205), effects that appear to be secondary to activity-induced increases in [Ca 2ϩ ] i that stabilize IRK1 mRNA (540). Chloride channels also contribute to resting conductance, particularly in skeletal muscle, and their development appears to be dependent on innervation-induced electrical activity (236,293,482).…”
Section: ؉ -Gated Channelsmentioning
confidence: 99%
“…In cardiac myocytes and renal epithelial cells, activation of PKC also produces an inhibition of Kir currents, although detailed functions of this inhibition are not fully understood (12, 19 -23). In addition to the covalent modulation of channel activity, PKC has also been shown to affect the expression of these Kir channels (15,24).…”
Section: Figmentioning
confidence: 99%